Multifocal origin of occupational cholangiocarcinoma revealed by comparison of multilesion mutational profiles. (20th June 2019) - Mimaki, Sachiyo; Watanabe, Masahiko; Kinoshita, Masahiko; Yamashita, Riu; Haeno, Hiroshi; Takemura, Shigekazu; Tanaka, Shogo; Marubashi, Shigeru; Totsuka, Yukari; Shibata, Tatsuhiro; Nakagama, Hitoshi; Ochiai, Atsushi; et al.
Abstract: Recently identified occupational cholangiocarcinoma among printing workers is characterized by chronic bile duct injuries and precancerous or early cancerous lesions at multiple sites of the bile ducts. These observations suggested the potential multifocal carcinogenesis of the disease. We performed whole-exome analysis of multiple lesions, including the invasive carcinomas and precancerous lesions of four occupational cholangiocarcinoma cases. A much higher mutation burden was observed in both the invasive carcinomas (mean 76.3/Mb) and precancerous lesions (mean 71.8/Mb) than in non-occupational cholangiocarcinomas (mean 1.6/Mb). Most somatic mutations identified in 11 of 16 lesions did not overlap with each other. In contrast, a unique trinucleotide mutational signature of GpCpY to GpTpY was shared among the lesions. These results suggest that most of these lesions are multiclonal in origin and that common mutagenic processes, which may be induced by exposure to haloalkanes or their metabolites, generated somatic mutations at different sites of the bile ducts. A similarly high mutation rate had already been identified in the precancerous lesions, implying an increased potential for carcinogenesis throughout the biliary tree. These genomic features support the importance of ongoing close follow-up of the patients as a group at high risk of recurrence. Abstract : Multilesion whole-exome analysis of four occupational cholangiocarcinoma cases was performed. A high mutation burden and a unique trinucleotide mutational signature without overlapping mutations were observed, suggesting genomic features of multifocal carcinogenesis of the disease.